UJI EFEK HIPOLIPIDEMIK EKSTRAK ETANOL KAYU SECANG (Caesalpinia sappan L.) TERHADAP TIKUS WISTAR (Rattus norvegicus) JANTAN - Rahman, Safriani; Kosman, Rachmat; Wijaya, Ika Indra (Fakultas Farmasi UMI, 2015)
Sappan wood contains brazilin compounds that acts as antioxidants to inhibit the cholesterol synthesis, so it is efficacious hypolipidemic. It has been conducted the research on hypolipidemic effect assay of ethanol extract of sappan wood against male wistar rats. This research aims to determine the hypolipidemic effect from the ethanol extract of sappan wood based on a decrease in cholesterol content of rats. This research used 15 male rats were divided into 5 groups. Group I (control) was given suspension Na. CMC 1%, group II (comparator) was given simvastatin, the groups III, IV, and V were given ethanol extract of sappan wood at a dose 75 mg/kgbw, 150 mg/kgbw, and 300 mg/kgbw. All provisions were done orally once a day for 14 days. Cholesterol content measurements were done at the beginning of cholesterol before induction, after induction and after treatment. Before treatment rats were induced with propylthiouracil 0.01% and high cholesterol diet. The results showed that the ethanol extract of the sappan wood has a hypolipidemic effect and a dose 300 mg/kgbw was not significantly different (p > 0.05) with simvastatin.